Filozofie analytická vs. kontinentální: na obranu dělení - Ivo Dragoun (Filozofia)
In his On the Very Analytic-Continental Division in Philosophy, Šebela presents three objections against dividing contemporary philosophy into analytic and continental. He calls them a factual objection, a methodological objection, and a power objection. In this paper, I will scrutinize the three objections and show that each of them ultimately fails. My motivation is to clear the theoretical path for those who wish to explore and reflect on the fascinating methodological presuppositions that constitute the division of contemporary philosophy into analytic and continental.